Penyuluhan Hukum dan Kesehatan tentang Bahaya Penyalahgunaan Narkotika, Psikotropika dan Zat Adiktif serta Dampak Kesehatan Mental pada Siswa dan Siswi di SMA Negeri 1 Warunggunung - Ulfi Jefri; M.Nassir Agustiawan; Defi Selvianita; Silvi Filya Sava; Hujatul Arifin; Hasan Siddiq; Mentari Salsabila (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The main aim of this social service is awareness and deeper understanding of the dangers of drugs, their legal and health impacts, as well as inspiring positive changes in attitudes and behavior in social settings among the younger generation and the general public. The service method used is legal advice, including legal sources from the police, doctors and public health workers. Activities carried out through communication include discussions, presentations and comparisons of legal aspects related to drugs. The results of this service show that anti-fraud training has succeeded in achieving its goals. Participants saw increased awareness of illegal drugs, their negative impact on health, and the legal consequences they face. Participants felt more responsible for their personal and community health. Information provides insight into prevention strategies to help participants develop healthy lifestyle skills and avoid high-risk behaviors.